Erroneous parallel gateways detection in BPMN models using fuzzy logic-based techniques - Kopp, Andrii Mykhailovych; Kudii, Dmytro (П. Голіней О. М., 2025)
The study presents an approach to automated detection of fault Parallel (AND) Gateways in Business Process Model and Notation (BPMN) models based on fuzzy logic. The proposed classifier uses feature vectors based on the topological properties of each gateway, including compliance with modelling rules, such as acceptable configurations of input and output flows. The results confirm the effectiveness of the approach for detecting structural errors in BPMN models and the potential of its application in real-life business model validation tasks.
Keywords: business process modeling; parallel AND-gateways; modeling errors; fuzzy logic; binary classification